Cantwell, Theresa Squires. Black and white photograph of two girls and a boy in a field from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra
Left to right: Theresa Marie Cantwell (Squires) age 5, Pat Squires age 3, Eileen Ottawa (Squires) age 4 in their parent's yard.